ACSM's guidelines for exercise testing and prescription - Pescatello, Linda S.; American College of Sports Medicine (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2014)
This book enables you to test and evaluate individuals to prescribe effective exercise programs tailored to their particular needs and based on the latest evidence. The text offers specific advice for working with individuals with cardiovascular, pulmonary, metabolic, and other diseases and health conditions so they can safely benefit from the advantage of exercise. You'll also learn clinically proven behavioral strategies for motivating people to exercise.
Benefits and risks associated with physical activity -- Preparticipation health screening -- Preexercise evaluation -- Health-related physical fitness testing and interpretation -- Clinical exercise testing -- Interpretation of clinical exercise test results -- General principles of exercise prescription -- Exercise prescription for healthy populations with special considerations and environmental considerations -- Exercise prescription for patients with cardiovascular and cerebrovascular disease -- Exercise prescription for populations with other chronic diseases and health conditions -- Behavioral theories and strategies for promoting exercise.
This book includes online access at http://thepoint.lww.com/active, please refer library staff for the password
Includes bibliographical references and index.
Keywords: Physical Exertion -- Guideline; Exercise Test -- standards -- Guideline; Exercise Therapy -- standards -- Guideline; Health and Wellbeing